FORMULATION AND EVALUATION OF SODIUM DICLOFENAC SLOW-RELEASE TABLET USING A COMBINATION OF MANGROVE FRUIT STARCH (BRUGUIERA GYMNORRHIZA) AND SODIUM CARBOXY METHYL CELLULOSE (CMC) AS MATRIX - NURWAINI, SETYO; ANGGRAINI, ANITA FITRI; SUKMAWATI, ANITA; IMANTO, TEGUH; UTAMI, WAHYU (International Journal of Applied Pharmaceutics, 2024)
Objective: Mangrove fruit (Bruguiera gymnorrhiza) has a high starch content that potential as a matrix for slow-release tablets. This study aims to determine the optimum formula for diclofenac sodium tablets using a matrix combination of mangrove fruit starch and sodium Carboxy Methyl Cellulose (CMC). Methods: Optimization of the formula was carried out using the Simplex Lattice Design method. Evaluation of the tablet includes the physical properties of the granules, tablet, and dissolution profile. Results: The combination of mangrove fruit starch of 15-45% and 0-30% CMC fulfilled the requirements for granule flow properties and the release of active substances. The optimum formula obtained was a combination of mangrove fruit starch 32.30% (193.80 mg) and 12.70% Na-CMC (76.20 mg) with a desirability value of 0.805. Conclusion: The results of this study clearly showed that the combination of mangrove starch and CMC was successfully used in the slow-release tablet formulation of diclofenac sodium